PENGARUH KOMPETENSI DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PADA PT. PERKEBUNAN NUSANTARA IV (PERSERO) MEDAN - Fadhillah, Andika; Aditi, Bunga; Hafas, Hafriz Rifki (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
The purpose of this study was to examine and analyze the effect of competence, work discipline and work environment on work performance at PT Perkebunan Nusantara IV (Persero) Medan partially or simultaneously. The approach used in this study is an associative approach. The population in this study are all employees at PT. Perkebunan Nusantara IV (Persero) Medan with 389 employees. Based on the calculation of sampling, the number of samples in this study were 115 employees of PT. Perkebunan Nusantara IV (Persero) Medan. Data collection techniques in this study used documentation, observation, and questionnaire techniques. Data analysis techniques in this study used a quantitative approach using statistical analysis using multiple linear regression, classical assumption test, hypothesis testing and coefficient of determination test. The results of this study prove that competence has a partial effect on work performance, work discipline has a partial effect on work performance, work environment has a partial effect on work performance. Competence, work discipline and work environment have a simultaneous effect on work performance at PT Perkebunan Nusantara IV (Persero) Medan